The twisted road to freedom : America's granting of independence to the Philippines - Carlson, Keith, 1966- (University of the Philippines Press, 1995)
"In analyzing the process by which the United States granted independence to the Philippines, rather than simply observing the effects of that process and then speculating backwards, Carlson attempted to provide new insights into the nature of the Filipino-American colonial relationship. A critical review of recently declassified American documents and the private papers of the key American officials involved in the decolonization process illustrates the inadequacies of past historical interpretations of the Filipino-American relationship. What emerges from these previously untapped sources is a fascinating tale of interdepartmental rivalries, competing private corporate and national interests, cross-cultural confusion, and personality conflicts."--BOOK JACKET.